Palmarès musicaux: où sont les femmes? - Vallet, Stéphanie (La Presse, 2019)

Gorgeous Girlies in Glittering Gyrations! Capital érotique et danse jazz dans l’entre-deux-guerres québécois - Blais-Tremblay, Vanessa (Recherches féministes, 2019)
Dans la littérature sur la danse exotique de la première moitié du xxe siècle, la danseuse noire apparaît soit comme la victime d’une industrie du divertissement capitalisant sur les mises en scène érotisantes, exotisantes et primitivisantes de son corps, soit comme la parodie subversive du stéréotype dit « primitif-exotique » incarné sur scène. Pour paraphraser bell hooks, le plaisir corporel, voire charnel, lié à la danse est avant tout abordé en tant que réalité à laquelle il faut résister, qui doit être masquée ou transcendée, ce qui force ainsi un processus de distanciation entre le travail artistique de la danseuse et le capital érotique de son corps. Dans cet article, l’auteure s’appuie sur une collection d’entretiens réalisés dans le contexte du travail de recherche ayant mené à la production cinématographique Show Girls: Celebrating Montreal’s Legendary Black Jazz Scene (1999) avec des danseuses qui travaillaient dans l’industrie du spectacle durant l’« âge d’or » du jazz montréalais (1925-1955). Les récits que révèlent ces entretiens permettent d’aller au-delà des questions de représentation dans la littérature sur la danse exotique pour poser un regard sur l’agentivité artistique de ces femmes qui résistent à la désarticulation entre leur travail artistique et le capital érotique de leurs corps.
Publisher: Revue Recherches féministes

L'improvisation jazz : une pratique fondamentale dans le processus de reconnaissance des musiciennes de Montréal - Champagne, Lysandre (Université du Québec à Montréal, 2019)
À partir des dimensions spatiale, temporelle et musicale, ce mémoire expose les modalités de reconnaissance des improvisatrices de jazz dans les jam-sessions de Montréal. En se référant au concept de Jeu chez Mead, l'autrice montre que l'authentification des musiciennes en situation d'improvisation est le produit de la communication mise en forme par ce type d'interaction. Toutefois, le contexte des jam-sessions montréalais maintient un «entre-soi» masculin défavorable à la reconnaissance des musiciennes comme improvisatrices distinctes dans ce jeu musical. Ainsi, l'improvisation dans ces événements de jazz participe à la reconduction des inégalités de genre.

Jouer les femmes : les concerts de musique contemporaine au Québec - Couture, Ariane (Recherches féministes, 2019)

Festivals de musique québécois : où sont les femmes ? - Croteau, Laurianne (Ici Radio-Canada, 2019)

Sexisme en musique : des trucs pour s’assurer une programmation paritaire et inclusive – Partie 1 - Daguzan Bernier, Myriam (Gazette des femmes, 2019)

Sexisme en musique : des trucs pour s’assurer une programmation paritaire et inclusive – Partie 2 - Daguzan Bernier, Myriam (Gazette des femmes, 2019)
Solutions constructives pour des rendez-vous musicaux plus vivants, diversifiés et… paritaires!

"A Jewish Maestra and a Lady too": Reflections on Femininity in the Career of Ethel Stark - Rachwal, Maria N. (Canadian Jewish Studies, 2019)
Ethel Stark (1910-2012) was one of the most important conductors and concert violinists in Canada in the Twentieth century. This article highlights how an Austro-Canadian Jewish woman who lived outside the constraints of conventional domesticity, both navigated through and defied the ideals of the “Cult of True Womanhood” and spearheads a movement of feminism in music. I argue that Stark’s exposure to Jewish cultural traditions of social justice and womanhood in her childhood formed a critical dimension of her feminist activism later in her life, and in particular in the founding of The Montreal Women’s Symphony Orchestra (1940).

Jazz, gender, historiography: a case study of the "Golden Age" of jazz in Montreal (1925-1955) - Blais-Tremblay, Vanessa (Université McGill, 2018)
This dissertation maps the interaction between jazz, identity, modernity and nation during the so-called "golden age" of jazz in Montreal (1925-1955). Drawing on the fields of musicology, women's studies (black feminist theory and feminist research methods in particular), critical dance studies, and cultural studies, this project provides a critical re-writing of the history of Montreal jazz, one which acknowledges various roles that racialized and ethnicized women played in the shaping of modern identities, pleasures and sounds in Quebec. Montreal's particular status as a "showtown" makes it a rich laboratory to study the collaborative creative relationships between jazz music and dance on the black variety stage in the first half of the twentieth century. I also map the specific parameters that articulate the discursive relationship between jazz and vice, in particular as these relate to the gendered and racialized embodiment of morality in interwar Quebec. Finally, this dissertation produces the first extensive biographical accounts and critical listening of several prominent Montreal-based female jazz artists, including pianists Vera Guilaroff and Ilene Bourne, all-girl groups such as The Spencer Sisters and the Montreal Melody Girls Orchestra, black women performers such as Tina Baines Brereton, Bernice Jordan Whims, Marie-Claire Germain, Mary Brown, Natalie Ramirez, as well as piano teacher Daisy Peterson Sweeney and dance teachers Ethel Bruneau and Olga Spencer Foderingham.

Laura Niquay. Vivre et s’affirmer au féminin attikamekw - Audet, Véronique (Cahiers du CIÉRA, 2017)

Partition pour femmes et orchestre. Ethel Stark et la Symphonie féminine de Montréal - Rachwal, Maria Noriega (Éditions du remue-ménage, 2017)
En 1940, deux femmes élégantes prennent le thé dans le lobby du Ritz-Carlton. Ne vous fiez pas aux apparences: leur rencontre annonce un grand chambardement dans l’univers de la musique classique. La mécène Madge Bowen et la violoniste Ethel Stark fondent à Montréal ce qui deviendra le premier orchestre symphonique canadien composé uniquement de femmes. […]

Bilan et perspectives sur la situation des compositrices au Québec : vers un décloisonnement des identités - Tremblay, Vicky (Les Cahiers de la Société québécoise de recherche en musique, 2017)
In the field of composition in Quebec, women composers are still less numerous than men composers. While the profession of composer has difficulty being recognized in Quebec society, women composers are twice as marginalized. Many of give evidence to the challenges they face when it comes to integrating into the musical community, and several musicologists have tried to better understand—and eventually solve—the problems specific to women in the field of composition.
Publisher: Société québécoise de recherche en musique

Entendu dans Cette ville étrange : « Fuck toute ! » – une génération de compositeur·e·s décomplexe sa marge - Henry, Symon (Circuit, 2016)
Publisher: Les Presses de l’Université de Montréal
Keywords: Pas sur genres ou/et sexualités

Changing openness and tolerance towards LGBTQ singer-songwriters - Williams, Katherine (The Cambridge Companion to the Singer-Songwriter, 2016)
Most often associated with modern artists such as Bob Dylan, Elton John, Don McLean, Neil Diamond, and Carole King, the singer-songwriter tradition in fact has a long and complex history dating back to the medieval troubadour and earlier. This Companion explains the historical contexts, musical analyses, and theoretical frameworks of the singer-songwriter tradition. Divided into five parts, the book explores the tradition in the context of issues including authenticity, gender, queer studies, musical analysis, and performance. The contributors reveal how the tradition has been expressed around the world and throughout its history to the present day. Essential reading for enthusiasts, practitioners, students, and scholars, this book features case studies of a wide range of both well and lesser-known singer-songwriters, from Thomas d'Urfey through to Carole King and Kanye West.

From Kitchen To Carnegie Hall: The Story of the Montreal Women's Symphony Orchestra - Rachwal, Maria Noriega (Second Story Press, 2015)
In the 1940s it was unheard of for women to be members of a professional orchestra, let alone play "masculine" instruments like the bass or trombone. Yet despite these formidable challenges, the Montreal Women's Symphony Orchestra (MWSO) became the only all-women orchestra in Canadian history. Formed in 1940, the MWSO became the first orchestra to represent Canada in New York City's Carnegie Hall and one of its members also became the first Canadian black woman to play in a symphony in Carnegie Hall. While the MWSO has paved the way for contemporary female musicians, the stories of these women are largely missing from historical records. From Kitchen to Carnegie Hall illuminates these revolutionary stories, including the life of the incredible Ethel Stark, the co-founder and conductor of the MWSO. Ethel's work opened doors of equal opportunity for marginalized groups and played an important role in breaking gender stereotypes in the Canadian music world.
Keywords: History / Canada / Post-Confederation (1867-); Music / History & Criticism; Music / Individual Composer & Musician

'The digital is everywhere': Negotiating the aesthetics of digital mediation in Montreal's electroacoustic and sound art scenes - Valiquet, Patrick Joseph (Université d'Oxford, 2014)
In this thesis I argue that the relationship between the increasing ubiquity of digital audio technologies and the transformation of aesthetic hierarchies in electroacoustic and sound art traditions is not deterministic, but negotiated by producers and policy-makers in specific historical and cultural contexts. Interviews, observations, and historical data were gathered during sixteen months of ethnographic fieldwork in the Canadian city of Montreal between 2011 and 2012. Research was conducted and analysed in collaboration with a transnational group of researchers on a programme of comparative research that tracked global changes to music and musical practice associated with digital technologies. The introduction presents Montreal as a rich ecology in which to track struggles for aesthetic authority, detailing its history as a key site of electroacoustic and sound art production, and its local positioning as a politically strategic 'hub' for the Canadian culture industry. Core chapters examine the specific role of digital mediation in the negotiation of electroacoustic and sound art aesthetics from multiple interlocking perspectives: the recursive relationship between technological affordances and theories of mediation; the mobilisation of digital technologies in the delineation of cultural, professional and generational territories; the political contestation of digital literacies and pedagogies; the articulation of the digital's opposition with analogue in the construction of instruments and recording formats; and the effects of the digital on the dynamics of genre and genre hierarchies. The concluding chapter offers a critique of the notion that digital mediation has shifted the balance between the normative and the generative dimensions of genrefication in the scenes in question, and closes by suggesting how a better understanding of this shift at an empirical level can inform an ongoing rethinking of the interaction between technology and aesthetics among scholars, policy makers, and musicians.

La Bolduc : une pionnière de l’émancipation des femmes au Québec - Dupuis, Andréann (Magazine Gaspésie, 2013)
Un article de la revue Magazine Gaspésie, diffusée par la plateforme Érudit.
Publisher: Musée de la Gaspésie

Inégalités et minorisation des identités chez les femmes artistes dans la francophonie canadienne - Robineau, Anne (Nouvelles perspectives en sciences sociales : revue internationale de systémique complexe et d'études relationnelles, 2013)
Even if women artists are wishing for recognition of their work, independently from their gender, language and belonging to a cultural group, their practices conditions are sometimes linked to these statuses. Through a sociodemographic study of French Canadian artists, we will analyze more specifically the data on women artists. We will show that, even if they have a higher education than man, women artists usually are considerably less paid for their services. We will also try to understand if minorization processes of women from professional artistic francophone communities can explain some gender inequalities and how the production of identity discourses (women, francophonie, linguistic minority) reinforce tensions between art and the identity perspective.
Publisher: Prise de parole
Keywords: Artiste; Artists; Canadian Francophonie; femmes; francophonie canadienne; inequalities; inégalités; minorisation; minorization; women

De la cuisine au studio - Lupien, Anna (Éditions du remue-ménage, 2012)
De la cuisine au studio explore les parcours de douze artistes issues de trois générations différentes : femmes signataires du manifeste Refus global en 1948, premières cinéastes qui ont œuvré à l’ONF dans les années 1970 et artistes médiatiques impliquées au Studio XX. À partir d’entrevues avec les artistes, Anna Lupien pose un regard sociologique sur l’expérience de créatrices qui ont investi l’art en tant qu’espace d’expression dans la sphère publique. De quelle façon ont-elles élaboré des stratégies créatives et par le fait même donné corps à des transformations sociales engendrées par le mouvement féministe, notamment en ce qui a trait à la conciliation travail-famille ? Comment ont-elles intégré des milieux artistiques qui ne leur étaient pas ouverts d’emblée ? Comment se sont-elles engagées pour le bien commun à travers leur parcours artistique ? Les histoires de ces artistes – Madeleine Arbour, Christine Brault, Mireille Dansereau, Dorothy Todd Hénaut, Stéphanie Lagueux, Bérengère Marin-Dubuard, Helena Martin Franco, Terre Nash, Anne-Claire Poirier, Françoise Riopelle, Bonnie Sherr Klein et Françoise Sullivan – témoignent des luttes inachevées du mouvement féministe et des brèches qu’elles ont pratiquées dans l’ordre des choses, suscitant des rencontres originales entre l’art et le politiqu

De la cuisine au studio : le rapport public/privé interrogé au fil des parcours d'artistes québécoises de trois générations - Lupien, Anna (Université du Québec à Montréal, 2011)

Quelle place pour les femmes dans la création musicale au XXIe siècle ? - Stévance, Sophie (Composer au XXIe siècle. Pratiques, philosophies, langages et analyses, 2010)

Reprise et intertextualité musicale. L’hommage à La Bolduc par des compositrices engagées vers l’avant - Stévance, Sophie (Volume ! La revue des musiques populaires, 2010)
Cet article étudie la notion de reprise sous l’angle de l’Hommage à La Bolduc rendu par sept compositrices à Mary Travers (alias La Bolduc), icône de la musique populaire au Québec dans les années 1930, à l’occasion du Festival SuperMicMac. Par des allusions, des références précises et explicites ou par de simples emprunts et citations, ces hommages sont autant de lectures que de relectures des chansons sélectionnées en abordant différents modes de jeux d’« intertextualité musicale ». Celle-ci se situe à deux niveaux : le pôle de la production, qui montre que les chansons engagées de La Bolduc sont elles-mêmes le témoignage d’une époque ; le pôle de la réception, pour exposer les résonances de ces chansons à partir de références autres et communes à la fois, comme la place des femmes dans la création musicale. Cette étude envisage ainsi la reprise à partir des aspects, des significations et des enjeux musicaux posés par l’intertextualité musicale, ici abordée sous l’angle de l’hommage alors conçu comme « réactivateur » de sens.
Keywords: concert / live / festival; féminité / masculinité / genre; intertextualité (musicale); politique / militantisme; reprise / pastiche / parodie; réception